Nuclear forensic analysis - Moody, Kenton James; Hutcheon, Ian D.; Grant, Patrick M. (CRC Press, 2015)
A multidisciplinary reference for forensic scientists, this book consolidates fundamental principles of nuclear forensic analysis, pertinent protocols and procedures, computer modeling development, interpretational insights, and attribution considerations into one convenient source. The authors focus particularly on the chemical, physical, and nuclear aspects associated with the production or interrogation of a radioactive sample. The material is presented with minimal mathematical formality and uses consistent terminology. Principles and techniques are discussed in terms of their applications.